JEJAK BUDAYA PENAJAM PASER UTARA DALAM CERITA ASAL USULNYA - Aquari Mustikawati (Kantor Bahasa Kalimantan Timur, 2019)
This research describes cultural traces of Penajam Paser Utara’s people through its origin consisting of value system, social norms, mindset, and work ethic of the people in the past. It discusses about cultural traces recorded in the origin of Penajam Paser Utara’s people. It uses library method to search data. It applies qualitative method to describe events in the past, like history, legends, or important events, including important figures that had ever existed. Cultural theory is used to analyze the culture of the people through their origin. The results of this study indicate that Penajam Paser Utara’s in the past recorded their local wisdom of each region on their origin. It can be concluded that Penajam Paser Utara’s origin can be used as knowledge to understand the history of the people so as to develop the potential of the region.